White Matter Hyperintensities Mediate the Negative Impact of HbA1c Levels on Cognitive Function - Rudolph Johnstone; Ida Rangus; Natalie Busby; Janina Wilmskoetter; Nicholas Riccardi; Sarah Newman-Norlund; Roger Newman-Norlund; Chris Rorden; Julius Fridriksson; Leonardo Bonilha (Brain Sciences, 2025)
Background: Type 2 diabetes is linked to impaired cognitive function, but the underlying mechanisms remain poorly understood. As white matter hyperintensities (WMHs) are common in diabetes and associated with vascular brain injury, we investigated whether WMH burden mediates the relationship between hemoglobin A1c (HbA1c) levels and cognition. Methods: We quantified WMH load using the Fazekas scale and conducted a mediation analysis with HbA1c as the independent variable, Fazekas scale as the mediator, and MoCA scores as the outcome variable. Results: WMHs partially mediated the relationship between HbA1c levels and MoCA scores (indirect effect = −0.224, 95% CI = −0.619 to −0.050, p = 0.001), accounting for approximately 15.6% of the total effect. Conclusions: This study suggests that WMHs partially mediate the association between chronically elevated blood glucose levels and cognitive impairment in neurologically healthy adults, supporting a potential microvascular mechanism in diabetes-related cognitive impairment.